2013
DOI: 10.4103/0974-2727.119862
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone Therapy in Staphylococcus aureus Infections: Where Do We Stand?

Abstract: Aim:The study aimed to evaluate the utility of various commonly used fluoroquinolones against Staphylococcus aureus isolates.Materials and Methods:A total of 250 isolates of S. aureus were studied from different clinical specimens like blood, pus, wound swabs, sputum, ear swabs, and body fluids between November 2009 and December 2011. All the isolates were tested for their susceptibility to fluoroquinolones and other antimicrobial agents by Kirby-Bauer disc diffusion method using criteria of standard zone of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 14 publications
(22 reference statements)
2
39
0
2
Order By: Relevance
“…We did not find a significant difference in infection profile between MRSA and MSSA isolates, mirroring the finding of Dilnessa and Bitew [21]. MRSA strains were found to be more resistant to non-beta lactam antibiotics compared to MSSA (Table 2), similar to findings of earlier studies [5,11,12]. Infection control practices need to be further strengthened and complemented with judicious antimicrobial prescribing to reduce the burden of MRSA infections.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We did not find a significant difference in infection profile between MRSA and MSSA isolates, mirroring the finding of Dilnessa and Bitew [21]. MRSA strains were found to be more resistant to non-beta lactam antibiotics compared to MSSA (Table 2), similar to findings of earlier studies [5,11,12]. Infection control practices need to be further strengthened and complemented with judicious antimicrobial prescribing to reduce the burden of MRSA infections.…”
Section: Discussionsupporting
confidence: 87%
“…Bouchiat et al, in their analysis of 92 S. aureus clinical isolates, found 70.6% (n=65) of them to be resistant to ciprofloxacin [11]. Gade and Qazi have reported 57.6% (n=144) isolates of S. aureus to be ciprofloxacin resistant [12]. High rates of quinolone resistance have also been noted earlier by Metri et al among S. aureus isolates (n=137) [13].…”
Section: Discussionmentioning
confidence: 60%
“…On iki Avrupa ülkesinden 78 laboratuvarla işbirliği içinde yürütülen bir çalışma, florokinolonlara direnç prevalansında büyük farklılıklar ortaya çıkarmıştır ve en yüksek direnç oranları %70.6 olarak MR-SA'larda kaydedilmiştir [28] . Klinik örneklerden Kirby-Bauer disk difüzyon yöntemi ile florokinolon direncini araştıran bir çalışmada MRSA izolatlarında siprofloksasin direnci %92.5 olarak bildirilmiştir [29] .…”
Section: Discussionunclassified
“…Studies have reported resistance to ciprofloxacin among MRSA ranging from 39% to 68%. (20) In a study by Neeta D Gade et al, (2013) ciprofloxacin resistant MRSA was 6.5%. (20) Agarwal et al, (2013) have reported 53.7% of the biofilm producing MRSA isolates as Ciprofloxacin resistant MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…(20) In a study by Neeta D Gade et al, (2013) ciprofloxacin resistant MRSA was 6.5%. (20) Agarwal et al, (2013) have reported 53.7% of the biofilm producing MRSA isolates as Ciprofloxacin resistant MRSA. (4) Biofilm producing bacterial isolates are recalcitrant to antibiotic therapy leading to chronic infection.…”
Section: Discussionmentioning
confidence: 99%